The Moderate Islam and Its Influence on Religious Diversity in Indonesia - Syafieh, Syafieh; Anzhaikan, M. (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2022)
This article aims to discuss the root of the discourse of religious moderation in various religious traditions in Indonesia. As a multicultural country with diverse ethnicities, races, religions, and cultures, religious tolerance is significant for maintaining religious harmony. Recently, the Indonesian government is greatly promoting and mainstreaming religious moderation programs to prevent any political tension and conflicts among religious groups. The government’s idea of religious moderation is seen as not accommodating all of the religious beliefs held by the Indonesian people. In this regard, this article examines how the language of religious moderation has evolved in each of various Indonesia’s religious traditions. Islam, Hinduism, Buddhism, Catholicism, Protestantism, and Confucianism are the official religions recognized by the state. Using discourse analysis, this study concludes that all the established religions in Indonesia essentially share the same notion of religious moderation, yet it is articulated in different terms.